Textual Thresholds and Their Significations in the Novel When the Sun Disappeared by Mamdouh Al-Ghali: A Semiotic Analytical Approach - Bouflaka, saifalislams mohamed (El Omda in Linguistics and Discourse Analysis, 2019)
The research seeks to provide accurate analytical treatment of the thresholds of the text in an interesting and contemporary novel published in 2017: "When the Sun Disappeared" by the Egyptian writer Mamdouh Al Ghali, I sought to analyze the thresholds of text in this narrative text, The analysis of this approach is the basis for highlighting the thresholds of the text in this novel. The importance of focusing on the thresholds of the text is reflected in the fact that it is the sanctuary that leads us to the realms of the text. It is the entrance to understanding the meanings, dimensions, backgrounds and worlds of the literary text. , Are linguistic constructs, and an iconic progression of the maton, and its tracking of Resulted in letters describing them know its contents, forms, and races, and push the reader to the conviction Bagtnaiha, and highlights include the: name of the author, title, and the cover image, and quoted, and submitted.